A system dynamics modelling assessment of water-energy-food resource demand futures at the city scale: Goma, Democratic Republic of Congo - Derrick Mirindi; Janez Sušnik; Sara Masia; Graham Jewitt (World Development Sustainability)
Understanding future demands of water, energy, and food (WEF) resources is essential to achieve sustainable management of these resources. Based on a survey of 90 households, this study provides an analysis of household water, energy, and food security for the city of Goma, Democratic Republic of Congo, where there is a lack of any such assessment. Water supply is largely unimproved. Electricity supply is fairly reliable in some parts of the city, but not others. Most residents rely on charcoal burning for food preparation. Dietary Diversity Scores are low indicating stable, but low food security. Data collected were used to develop an integrated WEF system dynamics model that was applied to simulate household-level resource demand. To assess future resources demand, four scenarios developed by the Global Scenario Group were simulated. Findings reveal that the 'Great Transition' scenario exerts lower impact on resources demand, representing the most likely trajectory to achieve sustainable socio-economic development and management. However, achieving the conditions required for a ‘Great Transition’ could be challenging in Goma, which is characterised by low incomes, poor access to resources, and the threat of armed conflict. To achieve greater efficiency in resources utilisation and to prepare for the future, a number of recommendations are made, including energy supply diversification, altered agricultural practices to diversify diets, and expansion and improvement of water supply infrastructure. This work provides a basis for similar assessments in DRC and central Africa, highlighting the need for integrated resources management and assessment for regional opportunities toward sustainable development.